(untitled) (TAJ: Journal of Teachers Association, 2019)
Nephrotoxicity, which is caused by mostly due to medication, is one of most important global health problem. Drugs are a common source of acute kidney injury. Drugs shown to cause nephrotoxicity exert their toxic effects by one or more common pathogenic mechanisms. . Most drugs found to cause nephrotoxicity exert toxic effects by one or more common pathogenic mechanisms. These include altered intraglomerular hemodynamics, tubular cell toxicity, inflammation, crystal nephropathy, rhabdomyolysis, and thrombotic microangiopathy. Drug-induced nephrotoxicity tends to be more common among certain patients and in specific clinical situations. Cisplatin, one of the many drugs, is responsible for severe nephrotoxicity. General preventive measures to avoid nephrotoxicity include using alternative non-nephrotoxic drugs; correcting risk factors; assessing baseline renal function before initiation of therapy, followed by adjusting the dosage; monitoring renal function and vital signs during therapy; and avoiding nephrotoxic drug combinations, using of several nephroprotective agents including medicinal plant extracts. Promising results showed that the use of some medicinal plant extracts (Dioscoreaalata and Moriengaolifera) gave rise to moderate restoration of normal physiology of kidney and liver of mice. TAJ 2018; 31(1): 46-51